Building Quality Of Life: Elderly With Hypertension - Rahmi, Upik; Gustina, Susi; Fitriana, Lisna Anisa; Putri, Suci Tuty; Darmawati, Irma; Pragholapati, Andria; Nasution, Lina Anisa (Indonesian Journal of Community Development, 2023)
Hypertension is a significant health issue among the elderly and is a major risk factor for cardiovascular diseases and other disorders. Factors such as unhealthy eating habits, lack of physical activity, stress, hormonal imbalance, and genetic predisposition significantly increase the risk of hypertension in the elderly. Integrated management, including regular blood pressure monitoring, appropriate pharmacological therapy, and an emphasis on healthy lifestyle changes, has proven to be effective in controlling and preventing complications of hypertension in the elderly population. The objectives of this activity are (1) to increase the knowledge and understanding of the community, especially the elderly, about hypertension and food management, and (2) to enhance the elderly's awareness of the importance of physical activity in maintaining their health. The results of the evaluation involving 20 participants showed an improvement in knowledge about hypertension, food management, and physical activity, and participants were motivated to prevent hypertension through proper food management and exercise.